Electrodynamics of the Low-latitude Thermosphere by Comparison of Zonal Neutral Winds and Equatorial Plasma Bubble Velocity - Chapagain, Narayan P. (Journal of Institute of Science and Technology, 2015)
The coincident observations of nighttime thermospheric zonal neutral winds and equatorial plasma bubble (EPB) drift velocities over Brazil during the October–December,2009 and 2010 are used to examine the coupling relationship between the thermosphere and ionosphere. The EPB zonal drift velocities are estimated using the airglow images recorded by optical imaging system, while the neutral winds are measured by using a bi-static Fabry–Perot interferometer (FPI) experiment deployed at two stations from Brazil. The results reveal the similar pattern in the EPB drift velocities and zonal neutral winds motion during the nighttime and night-to-night thereby illustrating a fully developed F-region dynamo. However, background natural winds also exceed EPBs velocities especially during the development phase of EPBs illustrating that F-region dynamo is not fully activated. Journal of Institute of Science and Technology, 2015, 20(2): 84-89